Population structure, genetic diversity and prolificacy in pishan red sheep under an extreme desert environment - Zhang, Cheng-long; Zhang, Jihu; Tuersuntuoheti, Mirenisa; Chang, Qianqian; Liu, Shudong (Frontiers in Genetics, 2023)
Extreme environmental conditions are a major challenge for livestock production. Changes in climate conditions, especially those that lead to extreme weather, can reduce livestock production. To explore the genetic mechanism of sheep prolificacy traits in Taklimakan Desert environment, genes and molecular markers screening is of great significance. We collected blood samples from healthy adult Pishan Red Sheep (PRS) and Qira Black Sheep (QR) living in this region by extracting DNA from jugular vein blood samples and preparing Illumina Ovine SNP50 chip. For PRS, linkage disequilibrium (LD) was calculated using the ovine SNP50 Beadchip and the effective population size (Ne) was estimated using SMC++. The genetic characteristics of PRS were analyzed by integrated haplotype score (iHS) and fixation index (F_ST). The result showed that r^2 of PRS was 0.233±0.280 in the range of 0–10 Kb and decreased with increasing distances. SMC++ tested that the Ne of PRS remained at 236.99 in recent generations. A total of 184 genes were screened out under iHS 1% threshold, and 1148 genes were screened out with F_ST under the 5% threshold, and 29 genes were obtained from the intersection of the two gene sets. In this study, the genetic characteristics of PRS and QR were compared by ovine genome chip, and the related excellent genes were searched, providing reference for the protection of sheep germplasm resources and molecular breeding in a desert environment.